Applying Al-Qawaid Al-Fiqhiyyah to Foster Youth Development in Alignment with Brunei Vision 2035 - Ibrahim, Ibnor Azli; Inderaani, Awangku Muhammad Hafiy Nasrullah Pg Hj; Moksin , Hayattuddin Hj; Amai, Norasiah Ag. Haji (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Al-Qawaid Al-Fiqhiyyah is one of the supporting methods in legal Istinbat. These principles are used by the jurists to make it easier for them to provide appropriate laws for problems that are diverse but have similarities. The challenges faced by the Islamic world today, including the country of Brunei Darussalam, require the input of ideas and a general framework to make it easier for a goal to be achieved. To what extent is Qawaid Fiqhiyyah able to provide useful input towards achieving Wawasan Brunei 2035. This study aims to find out how Qawaid Fiqhiyyah can develop teenagers who are in line with the goals of Wawasan Brunei 2035. This study was also made to find out several Qawaid Fiqhiyyah that can be used to frame a plan of action for the formation of adolescent personality and also to find out the steps needed so that they can achieve Wawasan's goals. Brunei 2035. To achieve this goal, this study will use library study methods. The results of this study found that Qawaid Fiqhiyyah is a method that can support the development of teenagers in this era in terms of management ideas and strategies.